2020
DOI: 10.1093/jxb/eraa339
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional reprogramming and enhanced photosynthesis drive inducible salt tolerance in sugarcane mutant line M4209

Abstract: Sugarcane (Saccharum officinarum L.) is a globally-cultivated cash crop whose yield is negatively affected by soil salinity. In the present study, we have investigated the molecular basis of inducible salt tolerance in M4209, a sugarcane mutant generated through radiation-induced mutagenesis. Under salt-contaminated field conditions, M4209 exhibited 32% higher cane yield as compared with its salt-sensitive parent Co86032. In continuation, M4209 displayed significantly higher leaf biomass in post-sprouting phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“… Li et al (2020) found that DEGs in potato were mostly enriched in functions such as transport activity and oxidoreductase activity under salt stress based on GO analysis and KEGG analysis. Similarly, the results reported by Negi et al (2020) found that when leaves of salt-tolerant and salt-sensitive sugarcane were subjected to transcriptome analysis and showed that sugarcane under salt stress induced genes related to metabolic processes, transmembrane transport, and photosynthesis expression, to reach a steady state in sugarcane production, thus increasing sugarcane yield under salt field conditions. Overall, genes of plants under inoculating with PSB may be regulated to cope with adverse growth conditions.…”
Section: Discussionsupporting
confidence: 56%
“… Li et al (2020) found that DEGs in potato were mostly enriched in functions such as transport activity and oxidoreductase activity under salt stress based on GO analysis and KEGG analysis. Similarly, the results reported by Negi et al (2020) found that when leaves of salt-tolerant and salt-sensitive sugarcane were subjected to transcriptome analysis and showed that sugarcane under salt stress induced genes related to metabolic processes, transmembrane transport, and photosynthesis expression, to reach a steady state in sugarcane production, thus increasing sugarcane yield under salt field conditions. Overall, genes of plants under inoculating with PSB may be regulated to cope with adverse growth conditions.…”
Section: Discussionsupporting
confidence: 56%
“…To assay the activities of antioxidant enzymes, total protein was extracted by homogenization of leaf/root tissue in chilled extraction buffer containing 100 mM potassium phosphate buffer (pH 7.0), 0.1 mM ethylene diamine tetra acetic acid (EDTA) and 1% polyvinyl pyrrolidone ( w / v ) and quantified. The activity of superoxide dismutase (SOD), ascorbate peroxidase (APX) Guaiacol peroxidase (GPX) and catalase (CAT) were estimated from the same extract according to protocol by [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Salt stress is one of the most important environmental factors, significantly decreasing crop growth and yield worldwide ( Zörb et al., 2019 ; Negi et al., 2020 ). Salt stress affects approximately 20 percent of all agricultural lands and 33 percent of irrigated agricultural lands ( FAO, 2017 ).…”
Section: Introductionmentioning
confidence: 99%